Early Childhood Care Education (ECCE) and National Security - Nungala Usman Isaac (Walidem Institute and Publishing, 2024)
This study explores the critical link between early childhood care education (ECCE) and national security. Early Childhood care education lays the foundation for future cognitive, social, and emotional development, which in turn, shapes a nation's human capital, social cohesion, and economic prosperity. A comprehensive review of existing literature and empirical data reveals that high-quality ECCE programs can mitigate risk factors associated with national insecurity, such as poverty, inequality, and social unrest. Conversely, inadequate ECCE can perpetuate cycles of disadvantage, undermining national stability and security. This study argues that investing in ECCE is a strategic imperative for national security, as it fosters a skilled and productive workforce, enhances social cohesion and community resilience, supports early intervention and prevention of social ills, promotes inclusive and equitable development and encourages a culture of peace, tolerance, and understanding. The study recommends that policymakers prioritize Early Childhood Care Education as a critical component of national security strategies, ensuring that all children have access to high-quality early childhood care and education.